Functional outcome of microsurgical clipping compared to endovascular coiling - Premananda Raja , Murugesu (2011)
Objective: Endovascular coiling has been used increasingly as an alternative to neurosurgical clipping for treating subarachnoid hemorrhage secondary to aneurysm rupture. The purpose of this study was to compare functional outcomes at 6 months post-subarachnoid hemorrhage secondary to cerebral aneurysm rupture in subjects who were either surgically clipped or endovascularly coiled. In addition, the present study aims to identify the predictors in the clinical course of aneurysmal subarachnoid hemorrhage. Materials and methods: A retrospective case review on the treatment methods of aneurysm rupture in Hospital Kuala Lumpur over the period of five years (2005-2009). A total of 268 patients who fulfilled the inclusion criteria were recruited for this study. These patients were broadly categorized into two groups based on their treatment mode for ruptured aneurysm. The case notes, CT brain films reports and angiography reports were analyzed with respect to their clinical, radiological, surgical clipping or endovascular coiling treatments and outcome data. Statistical analysis was determined using Chi-Square tests to study these associations. Results: There was a female predominance with male-to-female ratio 1:1.4. The mean age was 50.9 years old in this series. 50 patients were less than 40 years (18.7%) and 218 patients were more than 40 years(81.3%). 37 patients(74%) in age group less than 40 years had significant good outcome as compared to125(57.3%) patients above 40 years old.(p=0.03). One hundred and eighty one patients (67.5%) presented with Good WFNS (WFNS1-2) and 87 patients (32.5%) presented with Poor WFNS (WFNS 3-5) prior to intervention. One hundred and sixty two patients (60.4%) had good functional outcome (mRS grade 0- 2) as compared to 106 patients(39.6%) who had poor mRS outcome(MRS 3-6) while 50 patients died(18.7%) during our follow up at 6 months . When we analyzed the WFNS group with functional outcome (mRS), there was significant association (p<0.01). In good WFNS, 143(79%) had good outcome and in poor WFNS, 68 patients (78.2%) had poor mRS outcome. There were 204 (76.1%) patients in clipping group and 64 (23.9%) patients in coiling group. Patients who underwent coiling, initially showed a better mRS outcome with 47patients (73.4%) than, 115 patients (56.4%) in clipping. Further comparison showed that 89(43.6%) patients in clipping group had poor functional (MRS) outcome as compared to17 patients (26.6%) coiling, which was significant (p=0.015). However when we controlled the WFNS grade of presentation in the treatment groups, we obtained a different result. In good WFNS group, it was noted that 98 patients (76%) out of 129 patients in clipping group had a good MRS outcome while, 45 patients (86.5%) out of 52 patients in coiling group had good mRS outcome (p=0.114). In poor WFNS presentation, it was noted that in clipping group, 58 patients (77.3%) out of 75 had poor mRS outcome. Similarly with poor WFNS presentation, 10 (83.3%) out of 12 patient in coiling group had poor outcome. (p=1.00). Hence when we control the WFNS group, there was no significant association between treatment group (clipping and coiling) and mRS outcome at 6 months. Further we noted that age less than 40 and Fisher grade of 1-2 have better outcome while patients with EVD, CSF infection and pneumonia have poorer outcome. Using multiple logistic regression analysis we have determined that good mRS outcome is associated with good WFNS and absence of EVD Conclusion: Clinical severity of the SAH (WFNS grade) was the most significant predictor of functional outcome (mRS) at 6 months. Therefore the decision regarding treatment option needs to be individualized based on the presentation of the patient.